2001
DOI: 10.1002/jmv.2091
|View full text |Cite
|
Sign up to set email alerts
|

Community‐based seroepidemiological survey of HCV infection in Catalonia, Spain

Abstract: The objective of this study was to investigate the prevalence of antibodies against the hepatitis C virus (anti-HCV) and the associated risk factors in a representative sample of the population of Catalonia, Spain. Serum samples from 2,142 subjects aged between 5 and 70 years, selected at random from urban and rural habitats, were studied. Multiple logistic regression analysis was carried out to determine variables associated independently with the presence of HCV antibodies. The age and gender standardized pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
43
1
6

Year Published

2004
2004
2019
2019

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 85 publications
(55 citation statements)
references
References 35 publications
5
43
1
6
Order By: Relevance
“…In our samples, the prevalence of HCV serology was 0.6 %, a significantly lower figure in comparison to previous published studies (8)(9)(10)(11)(13)(14)(15)(16). We think that this figure is more in line with the current prevalence situation and that it has been affected by a rise of mortality from HCV that has been increasing since the 90s and by a fall of acute hepatitis proportion.…”
Section: Discussioncontrasting
confidence: 91%
See 4 more Smart Citations
“…In our samples, the prevalence of HCV serology was 0.6 %, a significantly lower figure in comparison to previous published studies (8)(9)(10)(11)(13)(14)(15)(16). We think that this figure is more in line with the current prevalence situation and that it has been affected by a rise of mortality from HCV that has been increasing since the 90s and by a fall of acute hepatitis proportion.…”
Section: Discussioncontrasting
confidence: 91%
“…In our study, a statistically significant relation between age and anti-HCV presence was confirmed in accordance to previous studies (12)(13)(14). Positive anti-HCV patients have also shown a liver test and GGT values significantly higher.…”
supporting
confidence: 93%
See 3 more Smart Citations